RANCANG BANGUN TURBIN REAKSI PADA SUNGAI TAMAN KOTA 2 DENGAN MODEL ALIRAN VORTEX - Insani, Chairil (Institut Teknologi Indonesia, 2021)
Electricity is a necessity that must exist today, its use is always subject to binding. Most of the electricity comes from fossil energy-based power plants such as PLTU. Therefore, a solution was made by making a vortex water turbine to produce electrical energy. Utilizing a river flow with a small head of water, the water will enter the cross section. The flow will form a vortex because the shape of the section and the draft tube makes the lower side of the section have lower pressure. The vortex turbine will be designed to use a permanent magnet 150 watt AC generator. With a cross section of 60 x 55 x 150cm, draft tube 9.6 mm and turbine blade 30 x 50cm made of aluminum. On the framework will be used a 3 x 3.5 cm strip plate which is rolled. In order to withstand the impact of water on the blade, a 7 mm shaft is used and a nominal bearing life of 10274 hours. The resulting rotation is continued with a pulley with a diameter of 30 mm, 180 mm and with a belt type V material JIS K 6323 A 34.